REKONSTRUKSI INDIKATOR KUALITAS PELAYANAN PUBLIK DIGITAL DALAM PERSPEKTIF NILAI PUBLIK: SUATU TINJAUAN LITERATUR - David Pagiel Laoli; Jefri Ardivo; Boni Saputra (STKIP Subang, 2026)
Public services in Indonesia face transformation pressures driven by the massive implementation of the Electronic-Based Government System (SPBE). Despite being framed as a solution to bureaucratic pathologies, SPBE evaluation predominantly operates under the New Public Management (NPM) paradigm, which positions technical efficiency as the sole criterion of success, thereby neglecting the essence of publicness and citizens' fundamental rights. The epistemological consequences of NPM dominance are consistently identified in contemporary literature: digitalization acceleration without inclusive social considerations has structurally widened the digital divide, systematically excluding marginalized groups from accessing fundamental state services. This study employs a Literature Review method covering 25 high-reputation journal articles published between 2020 and 2025, identified through Scopus, Web of Science, and SINTA (quartiles 1 to 3). Based on cross-cluster comparative synthesis, this study produces a novelty contribution in the form of a tripartite model of digital public service quality indicators grounded in Public Value Theory, comprising: (1) Inclusive Digital Service Performance; (2) Democratic-Political Value; and (3) Social-Ethical Value. The model is hierarchical and sequential, and recommends reforming SPBE evaluation instruments so that technology serves as an instrument of social justice rather than a bureaucratic end in itself.